Analysis of Logistics Quality on Customer Satisfaction in the E-Commerce Industry Using the SERQUAL Method and Kertesius Diagram - Irvan Nur Syarif; Usman Usman; Ida Farida; Imam Nuryanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Competition in the shipping service industry is becoming increasingly fierce with the rapid growth of e-commerce. Shipping companies are required to provide the best services in order to retain customers. J&T Express Boja Branch is one of the logistics service providers facing problems such as delivery delays, unfriendly administrative services, and carelessness in handling customer complaints, which have the potential to reduce customer satisfaction. The purpose of this study is to analyze the effect of logistics quality on customer satisfaction using the Service Quality (Servqual) approach and Cartesian Diagram. The research population consists of all J&T Express Boja Branch customers who have been determined. The research sample consists of 177 respondents determined using purposive sampling. Data was obtained based on questionnaires and analyzed using quantitative methods with validity, reliability tests and normality test as well as calculations of the gap between expectations and service performance. The results of the study show that, in general, the quality of logistics at J&T Express Boja Branch is considered good, but there is a gap between performance and expectations. The dimensions that need priority improvement are personal contact quality and order accuracy because they are considered important, but their performance is still below customer expectations. Meanwhile, the dimensions of order release quantities and order condition are considered satisfactory and need to be maintained. Other dimensions, such as information quality and ordering procedures, are considered reasonable, while order quality, order discrepancy handling, and timeliness are considered relatively better than other attributes